Efeito da carga cognitiva do pequeno jogo no desempenho tático em uma sessão de treino de jovens jogadores de futebol - Pedro Henrique de Almeida Oliveira (2024)
This study aims compare the passing decision-making performance and in-phase interpersonal coordination of soccer players subjected to small-sided games (SSG) with manipulated cognitive load after a training session. 24 male soccer players from the U-13 and U-14 categories (13.9 ± 0.9 years; 166.5 ± 9.7 cm; 57.8 ± 9.1 kg, tier 2) from two clubs in the state of Minas Gerais participated this study. Players were divided into teams based on their positional status and tactical performance. The study was divided into three phases: 1) Pre-test - a 4-min of 4-a-side SSG; 2) Intervention - three 6-min of 4-a-side SSG with the experimental protocols; 3) Post-test – similar to the Pre-test. Four protocols were performed: one control and three experiments protocols involving dual-tasks of counting passes, with progressive cognitive load: control, T1, T2, and T3, with T3 having the highest cognitive load, T2 higher than T1 and control, and T1 higher than control. Manipulation checks included: 1) perceived task difficulty; 2) error rate in pass counting. Passing decision-making was considered as the primary outcome of the study. The other primary outcome was the percentage of time spent in the In-phase interpersonal coordination pattern, recorded by 10 Hz GPS devices. For manipulation checks, a two-way repeated measures ANOVA was performed. ƞ2p and Cohen's d were used for effect size. Generalized Estimating Equations (GEE) were used to model the study variables (dependent variable: Post-test performance; covariate: Pre-test performance), followed by Bonferroni's post-hoc. The β coefficient was used as effect size. A significance level of p ≤ 0.05 was defined for all analyses. The results showed a decrease in passing decision-making performance from T1 to T3 (p = 0.002; β = 14.43). For In-phase interpersonal coordination, a decrease from control to T3 in the offensive phase (p = 0.011; β = 3.67) and an increase from T1 to T3 in the defensive phase (p < 0.001; β = 2.99) were observed. Therefore, it is concluded that performing SSGs with higher cognitive load induces an decline in offensive tactical performance after the training session. Additionally, due to the decline in offensive tactical performance, there is an improvement in defensive tactical performance after SSGs with higher cognitive load.